Strata: High-Performance Scalable Storage on Virtualized Non-volatile Memory - Cully, Brendan; Wires, Jake; Meyer, Dutch; Jamieson, Kevin; Fraser, Keir; Deegan, Tim; Stodden, Daniel; Lefebvre, Geoffrey; Ferstay, Daniel; Warfield, Andrew (12th FAST, 2014)
Strata is a commercial storage system designed around the high performance density of PCIe flash storage. We observe a parallel between the challenges introduced by this emerging flash hardware and the problems that were faced with underutilized server hardware about a decade ago. Borrowing ideas from hardware virtualization, we present a novel storage system design that partitions functionality into an address virtualization layer for high performance network-attached flash, and a hosted environment for implementing scalable protocol implementations. Our system targets the storage of virtual machine images for enterprise environments, and we demonstrate dynamic scale to over a million IO operations per second using NFSv3 in 13u of rack space, including switching.